The Analysis of Locutionary Act, Illocutionary Act, and Perlocutionary Act in Five Feet Apart Movie - Hilda Rismayanti (MEDIOVA: Journal of Islamic Media Studies, 2021)
This research is aimed to find out the types of speech act such as the locutionary act, illocutionary act, perlocutionary act and the influence of speakers's intention to the hearer in Five Feet Apart movie. This research uses descriptive qualitative method to give explanation in analyzed the data. The result of this research found three types of speech act, locutionary act, illocutionary act, and perlocutionary act that contain in the main characters. Locutionary act is the basic of utterance itself, the actual of the word. The illocutionary act also contain five kinds of type such as representative, directives, commisive, expressives, and Declarations. Nevertheless, the data findings show four kinds of illocutionary act. Declarations is kind of illocutionary act are not found in the utterances of the main characters since it needs a special circumtances to do. It means the speaker must have position in particular context to do this act. This study found various goals or intentions of illocutionary act by the speaker to the hearer, such as: stating, surprise, questioning, and refusal. Furthermore the perlocutionary act in this study get various effect by the speaker to the hearer based on the circumtances of each conversation. hearer could provide an appropriate and effective response to the speaker.